Comparative pyrolysis behaviors of tire tread and side wall from waste tire and characterization of the resulting chars. (15th February 2019) - Wang, Mengya; Zhang, Lei; Li, Aimin; Irfan, Muhammad; Du, Yanping; Di, Weiqiang
Abstract: In this study, tire tread (TT) and side wall (SW) of waste tire were separately used as feedstocks for pyrolysis treatment, and the resulting chars were thoroughly characterized to exploit the potential applications. Analytic results show that the SW contained higher fixed carbon (27.55%) and carbon content (82.30%) than those of TT (15.21% and 56.56% respectively). TGA results indicated that 400–600 °C is the main decomposition temperature range for both feeds. The char yields showed a declining trend and stabilized at 500 °C, and higher char yield of TT was achieved than that of SW. Meanwhile, the chars from TT showed a high surface area (121.47 m 2 /g) than that of SW (44.72 m 2 /g), which could be a good adsorbent or an activated carbon precursor. FT-IR results showed that leading surface functional group of TT-500 was C-O/C-O-C from alcohols, ketones or ether, whereas SW-500 from phenols, alcohols and carboxylic acids. When compared with commercial products, SW-500 showed better properties than those of a carbon black (N660, 10 μm) in terms of carbon quality and ash content. This study suggested that by pyrolyzing the distinct sections of the waste tire is a promising approach to produce chars for more specific applications. Graphical abstract: Image Highlights: Chars derived from tread and wall of tire poses different properties. Tire tread derived char showed high SBET than that of side wall. Component wise waste tire derived char is a promising approach for targeted chars.